Novel Bioactive Thio- and Semi-carbazide Ligands and Their Organotitanium(IV) and Organozirconium(IV) Complexes - DAVE, SAURABH; SINGHil, R.V.; JOSHI, S.C.; JAROLI, D.P. (Asian Journal of Chemistry, 2010)
Organotitanium(IV) and organozirconium(IV) complexes have been synthesized by the reaction of titanocenedichloride or zirconocenedichloride with two different ketimines in the presence of triethylamine. In all the reactions the imines behave as monobasic bidentate ligands. The resulting complexes Cp2M(L)(L') [where Cp = cyclopentadienyl ring, L = 2-[1-(2-thienyl)ethyledene]hydrazine- carbothioamide and L' = 2-[1-(2-thienyl)etbyledene]hydrazinecarboxamide, 2-[ 1-(2-naphthenyl)etbyledene ]hydrazinecarbothioamide, and 2-[1-(2-naphthenyl)etbyledene ]hydrazinecarboxamide have been characterized by elemental analysis and IR and 1H NMR spectral studies. Based on these spectral studies, an octahedral structure has been proposed for all the complexes. The antifungal, antibacterial and antifertility activities of the ligands and their complexes have also been carried out.